2018
DOI: 10.1039/c8sc02126k
|View full text |Cite
|
Sign up to set email alerts
|

Ring-opening hydroarylation of monosubstituted cyclopropanes enabled by hexafluoroisopropanol

Abstract: Ring-opening hydroarylation of cyclopropanes is typically limited to substrates bearing a donor–acceptor motif. Here, the transformation is achieved for monosubstituted cyclopropanes by using catalytic Brønsted acid in hexafluoroisopropanol (HFIP) solvent.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 51 publications
2
37
0
Order By: Relevance
“…On the contrary, lowering the temperature or loading amount of catalyst leaded to an increased proportion of 3 a (entry 6–9), and under the optimal conditions (entry 8), 3 a could be isolated in moderately high yield as the major product. We also optimized the reaction in 1,1,1,3,3,3‐hexafluoro‐2‐propanol (HFIP), which is known to exhibit excellent performance in the nucleophilic ring opening of DACs . We found that 2 a could be obtained in high yield with a catalytic amount of TfOH in diluted solution (entry 12), which is consistent with the common principal of intramolecular reaction.…”
Section: Methodssupporting
confidence: 63%
“…On the contrary, lowering the temperature or loading amount of catalyst leaded to an increased proportion of 3 a (entry 6–9), and under the optimal conditions (entry 8), 3 a could be isolated in moderately high yield as the major product. We also optimized the reaction in 1,1,1,3,3,3‐hexafluoro‐2‐propanol (HFIP), which is known to exhibit excellent performance in the nucleophilic ring opening of DACs . We found that 2 a could be obtained in high yield with a catalytic amount of TfOH in diluted solution (entry 12), which is consistent with the common principal of intramolecular reaction.…”
Section: Methodssupporting
confidence: 63%
“…Our group as well as many others have pointed out the enabling effect of solvents, such as hexafluoroisopropanol (HFIP) and nitromethane (MeNO 2 ), on Brønsted and Lewis acid catalyzed reactions through the formation of an H‐bond network. In the case of HFIP, we emphasized that the role of the catalysts was to significantly increase the acidity of an H‐bond cluster of HFIP, which was the true catalytically active species . Our reflections on the reactivity of arylboronic acids started during our investigations on the TfOH‐catalyzed arylative ring‐opening of unactivated cyclopropanes in HFIP (Table , entry 1.1) .…”
Section: Methodsmentioning
confidence: 99%
“…In the case of HFIP, we emphasized that the role of the catalysts was to significantly increase the acidity of an H‐bond cluster of HFIP, which was the true catalytically active species . Our reflections on the reactivity of arylboronic acids started during our investigations on the TfOH‐catalyzed arylative ring‐opening of unactivated cyclopropanes in HFIP (Table , entry 1.1) . We were puzzled by the reactivity of two catalyst systems typically used for activation of alcohols and oximes ( B1 and B3 ), as they were able to trigger the ring‐opening of phenylcyclopropane to generate product 1 (entries 1.2 and 1.5).…”
Section: Methodsmentioning
confidence: 99%
“…Another strategy to activate cyclopropanes takes advantage of their alkene-like reactivity, enabling electrophilic activation with Lewis acidic species. While efficacious protocols in this area have been recently disclosed 1419 , the scope of the nucleophilic components remains limited. Notwithstanding the advances outlined above, the development of protocols for the selective ring-opening and functionalization of non-activated cyclopropanes is a problem that is largely unsolved.
Fig.
…”
Section: Introductionmentioning
confidence: 99%